Validitas dan praktikalitas modul bermuatan CTL dan literasi lingkungan materi teori kinetik gas dan termodinamika kelas XI SMA - Shinta Kumala; Desnita Desnita; Asrizal Asrizal; Yenni Darvina (Universitas Negeri Padang, 2020)
This study aims to create a valid and practical CTL-charged module and environmental literacy used as a source of physics learning for high school class XI for kinetic theory and gas thermodynamics. The research objective is achieved by applying the development research model based on Sugiyono's design. Sugiyono's development design used consisted of seven stages of research. The validity test was conducted at the physics laboratory of UNP and the practicality test was conducted at SMAN 14 Padang. The instrument of validity was a questionnaire consisting of six aspects of assessment which were developed into 26 indicators and translated into 57 items of assessment. Practicality instruments for teachers and students contain four aspects of assessment consisting of 14 indicators and broken down into 37 points of assessment. The results of the validity test by three expert lecturers who gave an average value of 87.15 determined that the development module was valid with a very good level of validity. The results of practicality tests by teachers and students with an average value of 96.26 and 89.18. Based on the average value of practicality according to the teacher and student module development results can be said to be practical with a very good level of practicality. This shows that the module of practical development is used as a source of physics learning for class XI high school. Referring to the results of the validity and practicality tests that have been carried out it can be concluded that the resulting development module is suitable for use as a learning resource.